Effect of everolimus on the pharmacokinetics of octreotide long‐acting repeatable in patients with advanced neuroendocrine tumors: An analysis of the randomized phase III RADIANT‐2 trial. Issue 4 (29th December 2016) - Pavel, ME; Becerra, C; Grosch, K; Cheung, W; Hasskarl, J; Yao, JC
Abstract : In the RADIANT‐2 trial, addition of everolimus to octreotide long‐acting repeatable (LAR) exhibited a clinically meaningful 5.1‐month improvement in progression‐free survival (PFS) in patients with advanced functional neuroendocrine tumors. In this study, we characterized the effects of everolimus co‐administration on octreotide LAR pharmacokinetics and its relationship with efficacy and safety. At least one evaluable blood everolimus and plasma octreotide predose minimum concentration (Cmin ) was available for 182 patients and 294 patients, respectively. Concomitant everolimus administration increased octreotide Cmin with a geometric mean ratio (everolimus/placebo) of 1.47 (90% confidence interval [CI] = 1.32–1.64). Risk for progression was consistently reduced when everolimus Cmin was increased twofold, regardless of octreotide exposure (hazard ratio [HR] = 0.74; 95% CI = 0.46–1.18; HR = 0.54; 95% CI = 0.32–0.92 for 6 ng/mL and 4 ng/mL octreotide, respectively). Risk for pulmonary or metabolic events was associated with increased everolimus Cmin . Co‐administration of everolimus plus octreotide LAR increased octreotide Cmin, which did not impact efficacy.